Consumer’s Perception towards Use of Mobile Applications for Online Shopping in the Kathmandu Valley - Dhungana, Sashwat; Devkota, Niranjan; Paudel, Udaya Raj; Parajuli, Seeprata; Upretee, Sahadeb; Dhakal, Krishna; Mahato, Surendra (Quest Journal of Management and Social Sciences, 2022)
Background: Mobile devices have created a new channel for retailers to provide more targeted offerings to their customers. Online purchasing is the method of gaining knowledge of and purchasing merchandise or offerings over the Internet. Objective: This study aims to investigate online shopping users' perceptions by determining the factors that drive buyers towards shopping in the Kathmandu Valley. Methods: By adopting a descriptive and causal research design, the researchers collected data using non-probability sampling from 403 respondents in Kathmandu Valley with the help of KOBO Toolbox. A structured checklist is the main research instrument used for data collection. We analyzed the obtained data by using SPSS and AMOS software inferentially. For the hypothesis testing, we analyzed data using SEM. Results: SEM result indicates previous online shopping experience, and consumer lifestyle (CL) have a significant relationship with consumers' attitude (CA) and online purchasing intention (OPI). Conclusions: Consumers' perception towards online shopping differs according to their attitude, experience and lifestyle. However, poor quality of products, hidden costs and timely delivery of the products and services are major challenges faced by customers during online shopping. To ensure the growth of online shopping in Kathmandu Valley, the government should pay attention to legislation linked to online shopping, selling quality items and providing secure online payment.